Comparative study of double phototherapy (conventional plus biliblanket) verses conventional single phototherapy in the management of neonatal hyperbilirubinemia - Barua, Chiranjib; Shahidullah, Md; Mannan, MA; Noor, Khaled; Barua, Sharmila; Mutanabbi, M; Ali, Md Suhrab (Journal of Chittagong Medical College Teachers’ Association, 2009)
doi: 10.3329/jcmcta.v18i2.3826 Journal of Chittagong Medical College Teachers' Association 2007: 18(2):21-25